PENANGANAN PEMBIAYAAN BERMASALAH DI MASA PANDEMI COVID-19 DALAM FATWA DSN MUI (Studi pada Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) BTM Kajen) - Ayu Vianora, Natasha; Rosanti, Cholisa; Yohani, Yohani; Hudaya, Fadli (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
The purpose of this research is to find out, understand, and analyze the handling of murabahah and musyarakah financing carried out by the Savings Cooperative Sharia Borrowing and Financing (KSPPS) BTM Kajen during the COVID-19 Pandemic in the Fatwa DSN MUI. Since it is a descriptive qualitative study, some interviews, and observations were conducted. Data analysis is carried out by collecting, (data collection), reducing, (data reduction), presenting (data display), and drawing data conclusions or verification (conclusions). The results stated handling of problem financing of murabahah and musyarakah carried out by the Savings and Loans Cooperative and Sharia Financing (KSPPS) BTM Kajen during the COVID-19 Pandemic, including: (a) administrative process, conducted by rescheduling, reconditioning dan restructuring; (b) collateral, an agreement that has a guarantee at the beginning of the financing agreement murabahah is transferred under the name of KSPPS BTM Kajen until the financing has been payment by the customer; (c) settlement of disputes due to financing problems with murabahah and musyarakah financing are carried out in court. Furthermore, analysis settlement of problematic murabahah and musyarakah financing at KSPPS BTM is carried out in accordance with the Fatwa of the National Sharia Council- Indonesian Ulema Council (DSN-MUI). Associated with rescheduling, restructuring, reconditioning, guarantee auction, and write off of results interviews and also become the top ranking in financing settlement mapping the problematic murabahah conducted by the researcher, it was found that this solution model is in line with the DSN-MUI fatwa. REFERENSI Arifin, Imamul. 2015, Membuka Cakrawala Ekonomi, Jakarta: Setia Purna Inves. Azharsyah Ibrahim dan Arinal Rahmawati, 2017, Analisis Solutif Penyelesaian Pembiayaan Bermasalah di Bank Syari’ah: Kajian Pada Produk Murabahah di Bank Muamalat Indonesia Banda Aceh. Iqtishadia Volume 10 Nomor 1 2017. Azzahra, M., Yohani, Y., & Fatah, K. (2023). ANALISIS DAMPAK SEBELUM DAN DI SAAT PANDEMI COVID-19 TERHADAP HARGA SAHAM DAN LABA PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA. Jurnal Akuntansi STIE Muhammadiyah Palopo, 9(1), 1-14. Baswir, Revrisond. 2016. Manifesto Ekonomi Kerakyatan. Yogyakarta: Pustaka Pelajar. Dini, Melinda. 2020. Dampak Pandemi Covid-19 Terhadap Sektor Ekonomi. Jurnal Abdimas. Volume 7 Nomor 3, Maret 2021. Effendi, J. 2020. Mengembangkan Lembaga Keuangan Mikro Syariah. Semarang: UNDIP Gina, W., Effendi, J., 2014. Program Pembiayaan Lembaga Keuangan Mikro Syariah ( LKMS ) Dalam Peningkatan Kesejahteraan Pelaku Usaha Mikro (Studi Kasus BMT Baitul Karim Bekasi). Financing Program in Microfinance Institution ( LKMS ) of Welfare Enhancing for Micro Business Enterprise, 3(1), 33–43. Hanoatubun, Silpa. 2020. Dampak Covid 19 terhadap Perekonomian Indonesia. EduPsyCouns Journal, Volume 2 nomor 1, Universitas Kristen Satya Wacana. Jelitia, Wienanda Rizka Sukma dan Atina Shofawati, 2019, “Manajemen Risiko Operasional Pada PT Bank Pembiayaan Rakyat Syari’ah (BPRS) Jabal Nur Tebuireng Di Surabaya,” Falah: Jurnal Ekonomi Syari’ah, No. 1 (2019). Khairan, 2020. “Strategi Penanganan Pembiayaan Bermasalah Dengan Metode Reschedulling, Reconditioning dan Restructuring Pada Lembaga Keuangan Mikro Syari’ah Baitul Maal Wat Tamwil”. Jurnal At-Tamwil. Vol. 2 No. 1 Maret 2020. Kharisma, Widya Ratna. 2019. Manajemen Risiko Pembiayaan Mitra Usaha di KSPPS BMT al-Hikmah Cabang Mijen Ungaran. Jurnal. UIN Walisongo, Semarang. Lutfiani, A. P., & Hidayah, R. (2022). ESG Performance and Ownership Structure on Cost of Capital and Research & Development Investment. Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 21(1), 25-42. Risgiyanti, R., & Hidayah, R. (2020). The role of workplace spirituality in reducing the negative impact of organizational cynicism on job performance. Jurnal Aplikasi Manajemen, 18(4), 692-703. Riswan, R., & Suyono, E. (2016). Corporate diversification: Destroying or increasing firm value? Empirical evidence from Indonesia. Corporate Ownership & Control. 14 (4). Rosanti, C. (2020). Faktor-Faktor yang Mempengaruhi Inovasi Produk Koperasi Jasa Keuangan Syariah Pada KJKS BTM Se Jawa Tengah. Jurnal Ilmiah Ekonomi Islam, 6(1), 8-13. Usamah, U. (2022). THE MODERATION ROLE OF GENDER ON THE FINANCIAL PERFORMANCE OF BAITUT TAMWIL MUHAMMADIYAH IN INDONESIA. Jurnal Ekonomi & Bisnis Islam, 8(1).